This preview shows page 1. Sign up to view the full content.
Unformatted text preview: k42 = h*fxy2(t+h, Y1+k31, Y2+k32,k,D); k Y1new = Y1 + 1/6*(k11 + 2*k21 + 2*k31 + k41); Y2new = Y2 + 1/6*(k12 + 2*k22 + 2*k32 + k42); Y function f_xy1 = fxy1(t, y1, y2) f_xy1 = y2; f function f_xy2 = fxy2(t, y1, y2, k, D) f_xy2 = k*y1/D;...
View Full Document
This note was uploaded on 02/22/2010 for the course CHE 348 taught by Professor Chelikowsky during the Spring '08 term at University of Texas at Austin.
- Spring '08